Pengaruh Kecerdasan Emosional terhadap Kinerja Karyawan dimediasi oleh Kepuasan Kerja pada Puri Dajuma Beach Eco-Resort & Spa di Pekutatan Jembrana (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the effect of emotional intelligence on employee performance mediated by employee job satisfaction at Puri Dajuma Beach Eco-Resort & Spa in Pekutatan Jembrana. This study used a saturated sampling technique, with 50 employees of Puri Dajuma Beach Eco-Resort & Spa Pekutatan as respondents. Data analysis uses a structural equation model based on variance or a component based structural equation model (PLS). The results of the study explain that emotional intelligence and job satisfaction have a positive and significant effect on employee performance. Emotional intelligence has a positive and significant effect on employee job satisfaction. Employee job satisfaction is able to mediate the effect of emotional intelligence on employee performance. This gives an indication that employee job satisfaction should be a concern in improving employee performance at Puri Dajuma Beach Eco-Resort & Spa Pekutatan. For further research, should  to expand the scope of research, not only on the type of service companies but also on other types of businesses and can examine other variables that can affect employee performance in addition to emotional intelligence and employee job satisfaction